The The Effect of 5 Finger Hypnosis on Decreasing Stress Levels in the Family of Schizophrenia Patients in Puskesmas II Denpasar Timur - Wayan Sukma Wati; Desak Made ari Dwi Jayanti; Dewa Putu Arwidiana (NHM PRESS, 2021)
Stress is an unpleasant emotional reaction to real danger or imaginary that is accompanied by changes in the nervous system. The impact of people's stress is the IS, the Khawati is not calm, frustrated, angry, or nervous. One of the efforts to reduce stress on a person by giving hypnosis Therapy 5 fingers which is a form of self hypnosis purpose of this research to know the effect of hypnosis 5 fingers against the decline in stress levels in the family of schizophrenia patients in Puskesmas II East Denpasar. This research is a type of pre-experiment with the design of One-group Pre test Post Test Design with sample is 21 respondents, sampling techniques are purposive sampling. In pre-test results obtained as much as 19.05% of the data experienced mild stress levels and as many as 80.95% are experiencing moderate stress levels. After the 5-finger hypnosis therapy is obtained by post-test result data, which did not experience stress as much as 19.05% and which experienced a mild stress level of 80.95%. The pre-test and post-test results obtained a Z value of-4.025 with a signification value of P-value = 0.00. The value indicates there is a significant influence between before and after 5-finger hypnosis therapy to the level of the respondent's stress. Based on the results of this research that one form of therapy that can be applied to people with stress is with 5-finger hypnosis therapy.